Development of a miniaturized clamping device driven by magnetic shape memory alloys. (June 2014) - Wegener, Kathrin; Blumenthal, Philipp; Raatz, Annika
This article deals with the potential of magnetic shape memory actuators for the use in micro applications and in particular in clamping devices. The most common actuator concepts are introduced briefly, including the so-called push–push concept. Subsequently, an overview of clamping technology is given and the advantages of mechanical clamping are pointed out. It is proposed to use the push–push actuation concept for the development of an energy-efficient clamping device driven by magnetic shape memory alloys. Hence, the design of the magnetic shape memory clamping device and the dimensioning of its magnetic circuits are presented. Finally, the characteristics of the device are experimentally examined and the results are summarized.